2011
DOI: 10.1007/s00406-011-0219-1
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of spontaneous Parkinsonism in drug-naive patients with nonaffective psychotic disorders

Abstract: Spontaneous Parkinsonism (SP) in schizophrenia-related disorders is poorly characterized. The objective of this study was to examine the concordance and clinical validity of alternative definitions of SP in patients with nonaffective psychotic disorders. Two-hundred drug-naive patients with nonaffective psychotic disorders were examined for core parkinsonian signs, including bradykinesia, rigidity, and tremor, and diagnosed of SP according to the Simpson-Angus Scale (SAS) cutoff criterion, the UK Parkinson's d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 35 publications
3
12
0
Order By: Relevance
“…Our finding suggesting that spontaneous motor syndromes may predict treatment-emergent EPS are largely in keeping with previous studies ( 10 12 ). Whereas we found that spontaneous EPS is associated with treatment-emergent Akathisia, prior studies implementing a longer term follow-up of up to 24 months have demonstrated this relationship for treatment-emergent dyskinesia ( 13 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our finding suggesting that spontaneous motor syndromes may predict treatment-emergent EPS are largely in keeping with previous studies ( 10 12 ). Whereas we found that spontaneous EPS is associated with treatment-emergent Akathisia, prior studies implementing a longer term follow-up of up to 24 months have demonstrated this relationship for treatment-emergent dyskinesia ( 13 ).…”
Section: Discussionsupporting
confidence: 92%
“…To date, the three cross-sectional studies of the relationship between NSS and treatment-emergent EPS in never-medicated first-episode schizophrenia have reported conflicting findings ( 10 12 ). However, a previous finding of an association between baseline NSS and subsequent development of tardive dyskinesia (TD) ( 13 ), across 24 months observation of a multiracial African sample is profoundly important for the prevention of EPS in susceptible patient populations.…”
Section: Introductionmentioning
confidence: 99%
“…The association of UKU subscales with HRV parameters may be attributable to abnormalities in hypothalamic–pituitary–adrenal (HPA) axis activity in schizophrenia . A broad number of neuromotor abnormalities, particularly spontaneous parkinsonism, have been reported in drug‐naïve schizophrenia patients and these symptoms are closely related to decreased vagal activity . HRV therefore could be linked to HPA axis and parkinsonian manifestations, particularly hypokinesia and rigidity .…”
Section: Discussionmentioning
confidence: 99%
“…28,29 A broad number of neuromotor abnormalities, particularly spontaneous parkinsonism, have been reported in drug-naïve schizophrenia patients and these symptoms are closely related to decreased vagal activity. 30,31 HRV therefore could be linked to HPA axis 32,33 and parkinsonian manifestations, particularly hypokinesia and rigidity. 34,35 In contrast, there was no association between LUNSERS and any parameter of HRV in acute schizophrenia patients.…”
Section: Discussionmentioning
confidence: 99%
“…Spontaneous parkinsonism including bradykinesia, rigidity and tremor was investigated by Peralta et al [5] in 200 drug-naïve first-episode schizophrenia patients. The most frequent sign was rigidity, followed by bradykinesia, which was related to negative symptoms.…”
mentioning
confidence: 99%